SASCI-Mayo Clinic Fellows webinar: Vein graft interventions - Nel, E; Engelbrecht, A; Khan, S; Holmes, D; Barsness, G; Weich, H (SA Heart Journal, 2026)
This publication is the third instalment in a series of webinars conducted jointly by the South African Society of Cardiovascular Intervention (SASCI) and Mayo Clinic. Hosted by the regular faculty, the webinar began with an in-depth analysis of the pathogenesis of vein graft disease by Dr Barsness. It included a critical appraisal of published data supporting various interventional strategies in this patient population. His presentation was followed by a clinical case study by Dr Engelbrecht, focusing on a patient with recurrent acute coronary syndrome (ACS) events due to vein graft disease. Cardiology fellows from various South African universities participated as discussants. Objective: This manuscript, derived from the webinar series, summarises a multidisciplinary discussion of vein graft intervention complexities. It addresses the underlying pathophysiology, technical considerations, and current evidence- based management strategies. Case summary: A male patient with prior coronary artery bypass grafting (CABG) presented with recurrent episodes of ACS secondary to progressive vein graft disease. The discussion explored the pathogenesis of vein graft disease and the technical challenges of intervention, with a specific focus on the evidence and clinical considerations when deciding between vein graft and native vessel revascularisation. Following recurrent ACS events and percutaneous coronary intervention (PCI) attempts in the diseased vein graft, the patient eventually achieved successful revascularisation through a chronic total occlusion (CTO) procedure in the native left anterior descending artery (LAD).